Pengaruh Strategi Pembelajaran Relating, Experiencing, Applying, Cooperating, Transferring (REACT) terhadap Keterampilan Proses Sains Siswa - Syintia, Syintia; Akbar, Budhi; Safahi, Luthpi; Susilo, Susilo (Assimilation: Indonesian Journal of Biology Education, 2018)
This study aims to determine the effect of Relating, Experiencing, Applying, Cooperating, Transferring (REACT) learning strategies on students' science process skills. This research was carried out in SMA Negeri 11 Bekasi City from April to May 2017. The method used in this study was Quasi Experiment, with the Posttest Only Control Design research design. The target population is all students of class X MIA totaling 240 students. The sampling technique used Cluster Random Sampling, and obtained the X MIA 2 class as the experimental class and X MIA 3 class as the control class. Data collection is done by using multiple choice tests to measure 9 indicators of student science process skills. Hypothesis testing using the t test at a significance level Î± = 1%, obtained tcount = 3.06 t0.99 = 2.38, which means that H0 is rejected, so there is a very significant effect on both groups. So, it can be concluded that the use of REACT (Relating, Experiencing, Applying, Cooperating, Transferring) learning strategies has an effect on students' science process skills.